Functional Importance of Mini-Puberty in Spermatogenic Stem Cell Formation - Shima, Yuichi (Frontiers in Cell and Developmental Biology, 2022)
Primordial germ cells nesting in the fetal testis give rise to gonocytes. The gonocytes then transform into spermatogenic stem cells during the neonatal period and thereafter serve as a lifetime source of spermatogenesis. Therefore, gonocyte to spermatogenic stem cell (SSC) transformation is quite an important process that supports fertility in males. During the gonocyte to SSC transformation, morphological and transcriptomic changes sequentially occur and gonocytes migrate from the center to the peripheral region of the seminiferous tubules. However, extrinsic signals which trigger the transcriptomic changes as well as the migration are not yet fully clarified. Recent studies have drawn attention to the temporal activation of the hypothalamic-pituitary-gonadal axis during the neonatal stage which occurs concurrently with SSC formation. This phenomenon is called mini-puberty, and recent studies on human cryptorchid patients as well as animal models partially support the hypothesis that mini-puberty plays pivotal roles in gonocyte-to-SSC transformation. Focusing on this point, here, we aimed to discuss the latest knowledge on the importance of mini-puberty in spermatogenesis in this review.